DIDACTIC CONDITIONS OF USING DIGITAL TECHNOLOGIES IN TRAINING FUTURE ENGINEERS (International Congress on Economics, Management and Business Studies, 2026)
This article discusses the state of use of renewable energy sources in the Republic of Uzbekistan, current issues in ensuring sustainable development in the energy sector, and the problems of improving the system of personnel training in engineering. The authors analyze the didactic conditions for the use of digital technologies in the process of energy education and justify the need to strengthen the integration of education and production. Also, ways to develop the practical skills of future engineers through the introduction of innovative teaching methods in the higher education system, increasing the professional competence of teachers, and forming a digital learning environment are indicated. The article is aimed at increasing the efficiency of education and training qualified specialists in the competitive energy sector of Uzbekistan through the introduction of digital technologies.
Keywords: Digital technologies, engineering education, renewable energy, energy efficiency, innovative education, didactic conditions, information and communication technologies, advanced training, higher education, digital pedagogy.